Influence of sleep and meal schedules on performance peaks in competitive sprinters - Javierre, C.; Calvo, M.; Diez, A.; Garrido, E.; Segura, R.; Ventura, J. L. (International Journal of Sports Medicine, 1996)
The influence of sleep and meal schedules on performance in short distance running was assessed in a group of 8 national-class competition male sprinters. They were tested on Saturdays for five consecutive weeks. On each testing day, the performance time for an 80 m sprint was registered on eight different occasions during days 1 and 4, on 9 occasions on days 2 and 5, and on 7 occasions on day 3. On control days (days 1 and 4) performance gradually improved during the morning up to 13:00 h, decreased at 15:00 h, and again improved thereafter, with a maximum peak performance at 19:00 h. On day 2, in which sleep/wake cycles and meal-times were advanced for two hours, and on day 3, in which timetables were delayed for two hours, maximum peak performance was observed at 17:00 h and 21:00 h, respectively. At the time of maximum peak performance on both days a statistically significant improvement was observed as compared with the control day (day 2, p < 0.01; day 3, p = 0.001). On day 5, in which only the sleep/wake cycle was advanced for two hours, performance in the afternoon and evening was similar to that recorded on days 1 and 4. We observed that easy manipulation of sleep and meal schedules would allow competitive sprinters to synchronize peak power output with the time of the athletic event, increasing the chances for improvement in performance.